Aplikasi E-Commerce Business to Consumer Kartu Undangan - Tubagus Ahmad Darojat (JURIKOM (Jurnal Riset Komputer), 2019)
This study aims to to build an E-Commerce Business to Consumer application for online invitation card sales utilizing internet technology and payment facilities through paypal. System development methods that are used are E-commerce with flow analysis, Data flow diagrams (DFD). Results of research is an information system that handles order transactions, payments that can be made through paypal facilities, delivery of goods and return facilities so that it can help customers to obtain information about the products offered by UD Printing Matahari, facilitate customers in the process of ordering products, and can help improve sales for the company.